Towards robustness in neural network based fault diagnosis - Patan, Krzysztof; Witczak, Marcin; Korbicz, Józef (1951- ) (Zielona Góra: Uniwersytet Zielonogórski)
Challenging design problems arise regularly in modern fault diagnosis systems. Unfortunately, classical analytical techniques often cannot provide acceptable solutions to such difficult tasks. This explains why soft computing techniques such as neural networks become more and more popular in industrial applications of fault diagnosis.
Keywords: fault diagnosis; robustness; dynamic neural networks; GMDH neural network